Emergency obstetric hysterectomy: review at a tertiary care hospital - S. D., Shirodker; Pandey, Ankita; Yadav, Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of the study was to study indications and maternal outcome of emergency obstetric hysterectomy. Methods: A retrospective study of the cases of emergency obstetric hysterectomy performed over a period of 7.5years from 2008 to May 2016 in a tertiary care hospital was done. Maternal characteristics, indications, and maternal morbidity and mortality were analyzed. Results: During the study period there were 45 emergency obstetric hysterectomies and 28,207 deliveries, giving an incidence of 0.16% or 1.6/1000. Majority of the cases were unbooked (55.6%). It was more common in multipara (71.1%). Ruptured uterus (37.7%) and morbidly adherent placenta (26.6%) were the common indications. the maternal mortality was 2.22%. Conclusions: Emergency obstetric hysterectomy is a lifesaving procedure. The maternal outcome greatly depends on timely decision and good clinical judgment because unnecessary delay can cost life and undue haste can cause morbidity.